DAMPAK KEPAILITAN PENGEMBANG RUMAH SUSUN TERHADAP TRANSAKSI JUAL BELI RUSUN (STUDI KASUS RUSUNAMI KEMANGGISAN RESIDENCES) - Fennieka Kristianto (Problematika Hukum, 2015)
The uncompleted Flats construction and not provided the Certificate of Property Rights on Flats Unit (SHM Flats Unit) make Flats Unit’s purchaser only has the Conditional Sale and Purchase Agreement on Flats Unit (CSPA Flats Unit), therefore the Flats purchasers bear the consequences of bankruptcy on the developer. As a result of the bankruptcy of the Flats transaction raises legal issues related to the legal status of ownership of Flats Unit that  purchaser has paid the price. Do paid Flats Units become part of the bankruptcy estate of bankrupt developer? This paper aims to determine the impact of bankruptcy developer on flats’ purchasers and their legal status of the Flat Unit’s ownership  by  probing the case in Rusunami Kemanggisan Residences. This qualitative descriptive study, using research methods literature. Based on content analysis obtained the following conclusions. Bankruptcy resulted in a general seizure on properties of Flats developer, including Flats Unit which has been fully paid by the purchaser. The legal status of purchaser of  Flats Unit who has paid payment based CSPA Flats Unit,  not as owners, but as unsecured/concurrent creditors of the developer because it has not handed over the ownership of Flats Unit both factually and legally from the developer to the purchaser. As a result, the ownership rights of Flats Unit legally still on developer and become the developer’s bankruptcy assets. Suspension of Obligation for Payment of Debt  (PKPU) or mediation as an alternative dispute resolution is more favorable to developers and Flats purchaser.